Spontaneous Perinephric Hemorrhage Associated with Urolithiasis in Pregnancy - Leah P. McMann; Andrew C. Peterson; Sunil A. Ahuja (The Scientific World Journal)
Spontaneous perinephric hematoma in the absence of anticoagulation, arteritis, or trauma is uncommon. We report the case of a postpartum patient with nephrolithiasis who initially presented to the obstetric service with a spontaneous perinephric hemorrhage.